Improving Bilingual Literacy through Local Story Writing Workshop in Weekarou High School of West Sumba - Anna Sriastuti; Antonina Anggraini Setiamunadi; Yustina Priska Kisnanto (Journal Social Science And Technology For Community Service, 2026)
Education is one of the most crucial factors in building a nation. Literacy can be said as one of the main pillars to support the nation's education. As a country having a predicate of a low literacy level, Indonesia needs to improve its level by pushing students' reading interest and competency. Unfortunately, the lack of reading materials, especially literary works like short stories, worsened the condition of Indonesian students' literacy. Indonesia as a heterogeneous country with hundreds or even thousands should be able to provide the demands of reading materials using its own rich local cultures and traditions. This Community Service Program is a joint program between Faculty of Language and Art of Satya Wacana Christian University and Weekarou Christian Private High School of West Sumba to write local stories in bilingual, local language and Indonesia language. By involving students and teachers at the school in storybook writing training, students and teachers will not only improve their writing skills, but also deepen their understanding of local culture and local or regional languages. Students can document folk tales that are still oral stories into written form in their local or regional languages, while teachers play an active role in assisting the compilation of folk tales and the translation process, from regional languages to Indonesian.